Hollow carbon nanobubbles: Monocrystalline MOF nanobubbles and their pyrolysis - Zhang, W.; Jiang, X.; Zhao, Y.; Carné-Sánchez, A.; Malgras, V.; Kim, J.; Kim, J.; Wang, Shaobin; Liu, Jian; Jiang, J.; Yamauchi, Y.; Hu, M. (Royal Society of Chemistry Publishing, 2017)
© 2017 The Royal Society of Chemistry. While bulk-sized metal-organic frameworks (MOFs) face limits to their utilization in various research fields such as energy storage applications, nanoarchitectonics is believed to be a possible solution. It is highly challenging to realize MOF nanobubbles with monocrystalline frameworks. By a spatially controlled etching approach, here, we can achieve the synthesis of zeolitic imidazolate framework (ZIF-8) nanobubbles with a uniform size of less than 100 nm. Interestingly, the ZIF-8 nanobubbles possess a monocrystalline nanoshell with a thickness of around 10 nm. Under optimal pyrolytic conditions, the ZIF-8 nanobubbles can be converted into hollow carbon nanobubbles while keeping their original shapes. The structure of the nanobubble enhances the fast Na + /K + ion intercalation performance. Such remarkable improvement cannot be realized by conventional MOFs or their derived carbons.